North Atlantic mandates in the Danish Parliament, the Folketing - Harder, Mette Marie Stæhr (Politica, 2022)
Although the history and the future of the Danish Realm are currently questions of great political concern, and the Danish Folketing is an important arena for political life in the Realm, we know little about the North Atlantic mandates in the Danish Folketing. Most notably, we have no knowledge about the difference between the mandates from the Faroe Islands and Greenland: Do they participate in similar ways? Although North Atlantic MPs have acted quite similarly in relation to Danish government formation and have generally been most concerned with parliamentary affairs of specific interest to their homeland, there are important differences. Most notably, Greenlandic members have engaged almost twice as much in most parliamentary activities and they take much less leave.